The Role Of Intellectual Property And Value Creation In Career Sustainability: The Impact Of Collaboration In The Music Industry - Onodte, Jocely; Ongkowijoyo, Gracia (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
The rapid growth of Indonesia’s music scene has created challenges related to unfair royalty distribution and limited intellectual property protection. This study investigates how intellectual property and value creation influence the career sustainability of musicians, with collaboration as the mediating factor. A quantitative approach was applied, using a structured questionnaire distributed to 110 musicians across major cities such as Jakarta, Bandung, and Surabaya, resulting in 102 valid responses. The questionnaire aims to measure the perceptions of intellectual property management, value creation, and long-term career sustainability. Findings reveal that Value Creation’s impact on Career Sustainability is fully mediated by Collaboration. Collaboration itself has a significant positive effect on Career Sustainability. Conversely, Intellectual Property was found to have no significant impact on either collaboration or career sustainability, which may be due to inefficient royalty systems in Indonesia. These results highlight that collaboration is the critical mechanism transforming an artist’s value into long-term viability, supporting the Service-Dominant Logic framework. Future research should utilize larger samples and explore additional factors like digital platform policies.